Studying the effect of adding a thermoelectric generator to a hybrid car system to benefit from the heat of exhaust gases - عروس , هبه; نبيل غدير, (Latakia University Journal -Engineering Sciences Series, 2022)
The thermoelectric generator, by converting the heat of the waste gases into electrical energy, contributes to improving the fuel economy of hybrid cars, and this is what prompts us to study the effect of adding it to the hybrid car system. By analyzing the effect of the thermoelectric generator using Matlab software, we were able to determine the appropriate work pattern for the thermoelectric generator system associated with a hybrid car according to a specific range of speed, in order to achieve the greatest benefit from the heat lost with the exhaust gases, and this thus improves the performance of the hybrid car. Where the results showed that the car’s work in the charging mode suited the low speed values, while the engine type was suitable for the medium speed values, while the hybrid mode was suitable for the high speed values, and this shows the importance of switching between the three modes with the change of speed for the car to run in the best efficiency.